Annual review of comparative and international education 2020 - Wiseman, Alexander W., 1968- (Emerald Publishing Limited, 2021)
Since 2013, the Annual Review of Comparative and International Education has covered significant developments in the field of comparative and international education. The Annual Review of Comparative and International Education 2020 begins with a collection of discussion essays about comparative education trends and directions written by both professional and scholarly leaders in the field. Topics covered in this volume include major theoretical and methodological developments, reports on research-to-practice, area studies and regional developments, and the diversification of comparative and international education. A special introductory chapter examines the diversity in research trends in online versus traditional publications in the field and investigates the differences in content and representation among Global North and Global South research contributions.
Includes index.
Keywords: Comparative education -- Periodicals.; International education -- Periodicals.; Education -- Administration -- General.; Educational strategies & policy.; elektronické knihy; electronic books